THE LEGAL STATUS OF KASHUBIAN IN POLAND - SZWAJCZUK, Alina (Comparative Legilinguistics, 2013)
The objective of the article is to delineate the present status of the Kashubian language. The analysis will be based on the 2007 reports compiled by the Council of Europe with reference to the commitments made by Poland concerning the implementation of the European Charter for Minority or Regional Languages. In particular, the analysis will cover the provisions defined in Part III thereof with regard to Kashubian. The paper will try to assess whether the privileged status given to the Kashubian language has triggered significant changes in the treatment of the language by the Polish government and Kashubians. Do the reports prove that the language policy towards regional and minority languages within the European Union is in fact state-based? Do legislative grounds correspond with the change of attitudes of both the authorities and Kashubians?